1999
DOI: 10.1136/gut.44.5.643
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells are an important cellular source of tumour necrosis factor α in human intestinal tissue

Abstract: Background-Several inflammatory disorders of the intestine are characterised by enhanced expression of tumour necrosis factor (TNF-). Monocytes and macrophages have been suggested as a major cellular source of TNF-in human gut, whereas mast cells, although known to be capable of producing TNF-, have been poorly examined in this respect. Aims-To investigate whether human intestinal mast cells can produce TNF-, and which factors regulate TNF-production in these cells. (Gut 1999;44:643-652) Methods-Mast

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
117
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(121 citation statements)
references
References 45 publications
3
117
0
1
Order By: Relevance
“…All experiments were performed with mast cells cultured in the presence of SCF, because SCF is the only cytokine that provides human mast cell survival and is permanently present in tissues containing mast cells, thus presenting some kind of "physiological condition" as suggested earlier (18,35). Our data suggest that the expression of proinflammatory cytokines occurs constitutively in human intestinal mast cells and may be up-regulated following triggering of the cells with IgE-independent agonists such as bacteria (20). Activation of mast cells by IgE receptor cross-linking also results in an up-regulation of proinflammatory cytokines but in addition induces the expression of Th2-type cytokines.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…All experiments were performed with mast cells cultured in the presence of SCF, because SCF is the only cytokine that provides human mast cell survival and is permanently present in tissues containing mast cells, thus presenting some kind of "physiological condition" as suggested earlier (18,35). Our data suggest that the expression of proinflammatory cytokines occurs constitutively in human intestinal mast cells and may be up-regulated following triggering of the cells with IgE-independent agonists such as bacteria (20). Activation of mast cells by IgE receptor cross-linking also results in an up-regulation of proinflammatory cytokines but in addition induces the expression of Th2-type cytokines.…”
Section: Discussionmentioning
confidence: 73%
“…We found that Gram-negative bacteria are capable of enhancing TNF-␣ production in these cells by an IgE-independent means (20). The first evidence for the induction of TNF-␣ synthesis in mast cells by bacteria came from mice models.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations